(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A preliminary study on taxonomy of dactylopiids and the records of their hosts from Jalisco, Mexico was carried out. Three species of Dactylopius are present in this region: D. coccus, D. confusus, and D. opuntiae. It is necessary to collect additional specimens and from more host plant species to verify the presence of at least another two reported species: D. ceylonicus and D. tomentosus. This paper is the base to start a nation-wide taxonomic study on Mexican dactylopids.